Case Report: Zonisamide-induced DRESS syndrome with progression toward SJS: the first Chinese case and review of the literature on ZNS-associated SCARs - Wen, Juan; Du, Kang; Shi, Difang; Wang, Yue; Xue, Ruohong; Huang, Baogang; Liang, Xi; Fan, Huijuan; Xu, Fengming; Wu, Haohao (Frontiers in Medicine, 2025)
Zonisamide (ZNS), a sulfonamide-derived anticonvulsant, is increasingly used for epilepsy but remains an underrecognized cause of severe cutaneous adverse reactions (SCARs). This study reports the first documented case in China of ZNS-induced drug rash with eosinophilia and systemic symptoms (DRESS), which initially presented as painful papules and herpetiform lesions on the lumbar, abdominal, and facial regions. The patient also exhibited a potential risk of progression to Stevens-Johnson syndrome (SJS) in the context of acute liver failure. Notably, the patient’s latency period was 57 days, representing the second-longest interval reported in the literature. Furthermore, we provide a comprehensive review of ZNS-induced hypersensitivity reactions, including the clinical presentation, complications, management, and prognosis. Our systematic review of 30 ZNS-SCARs cases revealed key characteristics including a Japanese predominance (80%), a median latency of 23 days, and frequent hepatic involvement (26.7%), with human herpesvirus 6 reactivation confirmed in 66.7% of tested cases. Overall, 75% of patients improved following glucocorticoid-based therapies. This study aims to enhance awareness of SCARs associated with ZNS—including DRESS, SJS, and toxic epidermal necrolysis (TEN)—to support early recognition and timely clinical interventions.